2010
DOI: 10.1186/1472-6882-10-32
|View full text |Cite
|
Sign up to set email alerts
|

The design and protocol of heat-sensitive moxibustion for knee osteoarthritis: a multicenter randomized controlled trial on the rules of selecting moxibustion location

Abstract: BackgroundKnee osteoarthritis is a major cause of pain and functional limitation. Complementary and alternative medical approaches have been employed to relieve symptoms and to avoid the side effects of conventional medication. Moxibustion has been widely used to treat patients with knee osteoarthritis. Our past researches suggested heat-sensitive moxibustion might be superior to the conventional moxibustion. Our objective is to investigate the effectiveness of heat-sensitive moxibustion compared with conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…Among the sensations typically associated with the Deqi, penetrating heat, expanding heat, and transmitting heat were most common [22]. Being consistent with their prominent roles in TCM, bilateral Xi Yan (EX-LE5) and He Ding (EX-LE2) showed the most prominent sensations [13, 21]. …”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Among the sensations typically associated with the Deqi, penetrating heat, expanding heat, and transmitting heat were most common [22]. Being consistent with their prominent roles in TCM, bilateral Xi Yan (EX-LE5) and He Ding (EX-LE2) showed the most prominent sensations [13, 21]. …”
Section: Discussionmentioning
confidence: 97%
“…Previous studies manifested that the Deqi (heat-sensitive moxibustion sensation) was elicited in 70% of the moxibustion procedures of patients [21]. The frequency and intensity of individual sensations were significantly higher in KOA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these archaeological investigations were the embryonic form of moxibustion therapy and also the beginning of moxibustion analgesia [32]. It has been shown that moxibustion could effectively treat human primary dysmenorrheal [33], knee osteoarthritis [34], rheumatoid arthritis [35], and cancer pain [36]. However, the mechanisms of moxibustion analgesia are not elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In the process of moxibustion treatment, the researchers discovered that, when human body is in morbid condition, related acupuncture points were quite sensitive to moxa's heat and produced nonlocal or nonsuperficial heat sensation, such as penetrating heat, expanding heat, and transmitting heat [15]. This phenomenon resembles the one that occurs when the Deqi appears after moxibustion rather than local heat sensation and surface glow of the skin.…”
Section: Introductionmentioning
confidence: 99%